Reflections concerning spurfowl and francolin species recommendations contained in Mandiwana-Neudani et al. (2019a and 2019b). (8th June 2021) - Hunter, Nigel; Turner, Don; Borrow, Nik; Finch, Brian; Scott Kennedy, Adam; Stevenson, Terry; Baker, Neil; Redman, Nigel
Abstract : Recently, two papers by Mandiwana-Neudani et al. (2019a, 2019b) revisited the taxonomy of all Afrotropical spurfowl and francolins and proposed significant changes at the species level. A careful review of the papers suggests there are key deficiencies and inadequate explanations in both. These concerns include doubts about the methodology employed and the proposed taxonomic changes for some 13 species in particular. The methodology employed by the authors is a combination of an 'organismal' matrix consisting mainly of plumage patterning, wing/tail/soft part measurements and vocalisation indicators, all allocated a score and then combined with some DNA analysis. For the non-molecular work, there is no explanation of the scientific basis used for the scoring characteristics and the scores allocated. There is also no explanation as to why 33 features were used in the spurfowl paper and only 24 in the francolin paper, particularly where no reference has been made to the age or sex of the birds scored and compared. A concern in the DNA component is that the number of samples is far too few for justifying a significant taxonomic rearrangement covering the whole of Africa. There does not appear to be a single taxon that is represented by more than one genetic sample, which is well outside the norm for robust studies and does not allow for mistakes in the sample labelling or analysis to be detected. In addition to the above concerns, there are many factual errors in both papers pertaining to the text and distribution maps and these are detailed in the individual species' comments. Based on this analysis, there seems to be good justification in recommending that their taxonomic results and conclusions should be treated with care and caution until additional research is undertaken.